Live three-dimensional echocardiography: imaging principles and clinical application. - Wang X; Deng Y; Nanda NC; Deng J; Miller AP; Xie M (Echocardiography, 2003)
Live three-dimensional echocardiography (L3DE) is an important breakthrough in the field of medical ultrasound. It will provide a great potential tool for clinical diagnosis and treatment. In this article, the authors first review the bottlenecks in 3D cardiac imaging and the technical principles of L3DE that have been used to overcome some of these problems. We then discuss the scanning methods, clinical usefulness, and the future of L3DE, drawing on our experiences in examining 124 human patients and in conducting animal verification studies with a live 3D ultrasound system.